IMPLEMENTASI APLIKASI SITATA BERBASIS WEB UNTUK MENINGKATKAN EFEKTIVITAS TRACKING BERKAS PADA KANTOR PERTANAHAN KOTA JAMBI - Viera Tri Agustine; Sepriano; Syafarudin; Isnaini Saputra; Subhan Dani Saputra; Imelia Dwiyanti; Rizki Surya Ramadhan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information technology has encouraged government agencies to improve the quality of administrative services, including the Jambi City Land Office, which has implemented a web-based application called SITATA (File Receipt Flow Tracking System) to facilitate the document-tracking process. Prior to the system's implementation, file monitoring was carried out manually using log books and physical forms, making the process of searching, tracing, and monitoring file status less effective and prone to document loss. This study aims to examine the implementation of the web-based SITATA application in improving the effectiveness of file tracking at the Jambi City Land Office. The research employed a descriptive qualitative method, with data collected through direct observation, interviews, documentation, and literature study during the internship period. The system was developed using the Prototype model, while functional testing was conducted using the Black Box Testing method with an Equivalence Partitioning approach on 38 test cases. The results show that all 38 test cases (100%) produced outcomes consistent with expectations, and the SITATA application proved effective in supporting the recording, searching, and monitoring of file status more quickly, systematically, and transparently compared to the previous manual process. The implementation of this application has the potential to improve employee work efficiency and optimize land administration services for the public.